Epigenetics of chronic inflammatory diseases - Stylianou E (Dove Medical Press, 2018)
Eleni Stylianou Consultant Biomedical Scientist and Bioinformaticist, North Royalton, OH, USA Abstract: Chronic, noncommunicable, and inflammation-associated diseases remain the largest cause of morbidity and mortality globally and within the United States. This is mainly due to our limited understanding of the molecular mechanisms that underlie these complex pathologies. The available evidence indicates that studies of epigenetics (traditionally defined as the heritable changes to gene expression that are independent of changes to DNA) are significantly advancing our knowledge of these inflammatory conditions. This review will focus on epigenetic studies of three diseases, that are among the most burdensome globally: cardiovascular disease, the number one cause of deaths worldwide, type 2 diabetes and, Alzheimer’s disease. The current status of epigenetic research, including the ability to predict disease risk, and key pathophysiological defects are discussed. The significance of defining the contribution of epigenetic defects to nonresolving inflammation and aging, each associated with these diseases, is highlighted, as these are likely to provide new insights into inflammatory disease pathogenesis. Keywords: epigenetics, nonresolving inflammation, inflammatory diseases, atherosclerosis, type 2 diabetes, Alzheimer’s disease